(untitled) (Applied Biological Research, 2023)
Boric acid is a well-known wood preservative and fire retardant having low mammalian toxicity. Its efficacy is affected as it is non-fixed type, water leachable and effective only in interior conditions. In present study the effect of silicic acid and treatment methods on permanency of boron in plywood was studied through leaching test. The plywood was treated with glue line treatment as well as veneer treatment method with boric acid and three combinations of boric acid and silicic acid (1:1, 2:1 and 3:1) at 2, 3 and 4% concentrations.With a view to explore the possibility of fixation of boric acid in combination with silicic acid, the treated samples were subjected to leaching and then boron content was analyzed in leached samples. The results showed that boron was easily leached from the samples treated with boric acid only; whereas the treatment with the combination of silicic acid improved boron fixation in samples. The results of two different treatment methods showed suitability of veneer treatment to achieve sufficient boron retention in plywood. However, the leaching of boron was also high in veneer treatment than glue line treatment method.